Study of Entrepreneurial Values in Social Entrepreneur: A Case Study on Social Enterprise Misteripang (A Social Science and Entrepreneurship Journal, 2023)
values in social enterprise Misteripang. This research is adescriptive study with a qualitative approach that aims toexamine the entrepreneurial values that exist in the SocialEntrepreneur Misteripang. The variables in this study areentrepreneurial values in the Social Entrepreneur Misteripangwhich consist of being independent, creative, risk-taking,action-oriented, leadership and hard work. The participant orsubject of this research is the owner of the Misteripang.Methods of data collection using in-depth interviews,documentation and literature study. The results of this studyexplain that: 1) There are six main entrepreneurial values inOwner Misteripang, namely independent, creative, risk-taking,action-oriented, leadership, and hard work. 2) Finding newentrepreneurial values from Misteripang entrepreneur, namelycooperation and communicativeness. 3) Entrepreneurial values that need to be improved are action-oriented.
Keywords: Mysterious Pang; Social Enterprise; Entrepreneurial Values